Dubček, 3rd from the right on the front row on the above photo, is skipped out after August 1968 on the photo below. Text on the back. Photo issued on the occasion of an exhibition on freedom of press in Amsterdam
Dubček, 3rd from the right on the front row on the above photo, is skipped out after August 1968 on the photo below. Text on the back. Photo issued on the occasion of an exhibition on freedom of press in Amsterdam.